The Effect of Holistic Comprehensive Health Service Approach Through Family Functions on Optimizing the Nutrition Status of Junior High School Students - Febri Endra Budi Setyawan; Carla Edhina Widiadi (Saintika Medika, 2020)
Background : Nutritional status problems have many causes, including genetic, body metabolic conditions, behavior, environment, culture, and socioeconomic factors. One environmental factor that receives relatively limited attention is that children are exposed to undue stress, especially family stress. One of the factors influencing a child's nutritional status is his family. Family functions that run well can optimize the process of growth and development of children which can be described by the nutritional status. Optimization of nutritional status in children can not only be done from a clinical approach alone but needs holistic comprehensive management.Objective : The purpose of the study was to analyze the effect of a holistic comprehensive health service approach through family functions on optimizing the nutritional status of junior high school students.Method : This study was an observational analytic study with a cross sectional approach with the subjects of Malang City's "Z" Junior High School  students. Implementation in May- August 2019. The research subjects were 265 people with multistage random sampling. Data collection by interview. The analysis is displayed in the form of frequency distribution and correlation using the Spearman test and logistic regressionResults and Discussion : Family function is quite influential on nutritional status (r = 0.445). In logistic regression, the equation Y = 8.563-0.582X1 - 0.992X2-0.606X3 is obtained. The most  influential family function is partnership of 99.2%. Partnership describes communication,  mutual sharing, mutual complementarity between  family members in  all problems faced by family members, as well as the level of deliberation in making decisions and or resolving a problem that is being faced with other family members. Comprehensive holistic health service approach is sufficient effect on nutritional status (r = 0.463).Conclusion : The holistic comprehensive health service approach gives sufficient influence on the nutritional status of students in Malang City's "Z" Junior High School.